Morpho-environmental strategies in the genus Ononis L. (subsections Natrix and Viscosae) in Western Mediterranean. (2nd January 2018) - Rocha, J.; Ramírez, R.; Díaz, M.; Martins, M.; García-Cabral, I.; Amich, F.; Almeida, R.; Carnide, V.; Castro, I.; Crespí, A. L.
Abstract: Very similar morphologies have always been pointed out for subsections Natrix and Viscosae of the genus Ononis L. Morphological, environmental and biogeographic approaches do not show significant differences between taxa of both subsections, and only life form was pointed out as biological descriptor to explain taxonomic and ecological strategies for these taxa : Natrix is composed by perennial life forms, while Viscosae is solely represented by annual life forms. The discussion of results was conducted through the insurance hypothesis, according to which resilient or resistant behaviours, here represented by taxonomic diversity and morpho-environmental variability, described the ecological strategies for these taxa . In this way, wider morpho-environmental variability induced more responses (higher taxonomic diversity and life forms), i.e. more resilience. On contrary, the narrower morpho-environmental variability induced less taxonomic diversity and only perennial life forms, i.e. more resistance. Two future climate change scenarios were also used to confirm these resilience and resistance strategies for both subsections.